Urgensi Materi Bela Negara Dalam Kegiatan Pengenalan Kehidupan Kampus Bagi Mahasiswa Baru Di Perguruan Tinggi - Lutfiana, Rose; Rizki, Ascosenda Ika (Penerbit STKIP PGRI Bangkalan, 2020)
Defending the state is an obligation that must be carried out by every Indonesian citizen. This is in accordance with the mandate of the Indonesian state constitution of the 1945 Constitution of the Republic of Indonesia. The purpose of this study is to analyze the urgency of state defense material in the introduction of campus life for new students in tertiary institutions. The approach and type used in this research is qualitative literature study. The results obtained are the provision of state defense materials at the time of introduction to campus life for new students is mandatory in accordance with the general guidelines for introduction of campus life for new students No. B / 636 / B.B3 / KM.00 / 2019